Action in action research: Elaborating the concepts of action, roles and dilemmas in a public e-service development project. Issue 2 (9th May 2016) - Melin, Ulf; Axelsson, Karin
Abstract : Purpose: The purpose of this paper is to elaborate on the concept of action by addressing actions and roles in the practice of action research, illustrated by dilemmas in an action research project on information systems development in public sector. The main ambition with action research is being able to solve organisational problems through intervention and to contribute to scientific knowledge. The main emphasis has so far been on the "research part". Here the authors focus on the "action part" of action research to generate rigorous research, to solve local problems and to deal with evident dilemmas in action research. Design/methodology/approach: This is a qualitative case study. The empirical illustrations of this paper originate from an action research project that focused the two e-service development initiatives analysed below. The analysis is structured using key aspects and phases proposed by Avison et al. (2001). As a result of the analysis, the concept of action is elaborated. The action elements action, actor, motive, space and time are analysed together with different roles. This goes beyond the existing action research literature. Findings: The conclusions show that there is a need to understand actions and roles within action research projects – not separating action from research. Research is also seen as action. The practice of action research is also discussed as context-bounded interactive social action: action research as a recurrent, interactive and dynamic activity. It is also identified that the understanding of roles, actions and interaction can help handle dilemmas in action research. Research Limitations/implications: The authors contribute to the body of knowledge concerning action research in the information systems research field and in general by exploring the need to study the concept of action (e.g. situations and elements), to be explicit concerning the different phases, roles and responsibilities and management of different dilemmas in action research. A limitation of this study is that the inter-organisational development character in this study adds an extra dimension into the practice of actions research only partially highlighted. Another limitation is focus on public agencies. However, this is not critical for the results on action elements and the action research dilemmas that are studied. Practical Implications: The understanding of roles, actions and interaction can solve the dilemmas and challenges linked to the practice of action research in the information systems field, but such understanding can help discover and handle dilemmas in action research. Originality/value: The originality in this research is an illustration of and a perspective of action research as a context-bounded interactive social action: action research as a recurrent, interactive and dynamic activity. The value is that this knowledge can help handle dilemmas in action research.